When and where are livestock climate-smart? A spatial-temporal framework for comparing the climate change and food security synergies and tradeoffs of Sub-Saharan African livestock systems - Germer, Leah A.; van Middelaar, Corina E.; Oosting, Simon J.; Gerber, Pierre J. (Agricultural systems, 2023)
The livestock sector in Sub-Saharan Africa (SSA) is under increasing pressure to define its role in jointly addressing food security and climate change. Climate-smart agriculture (CSA) has been widely leveraged as an approach to achieving both food security and climate change outcomes through suites of interventions that maximize synergies and reduce tradeoffs among three pillars: productivity, climate change resilience, and climate change mitigation. However, operationalization of the CSA approach in the livestock sector is hindered by a lack of clarity around what the pillars mean for livestock systems, given their fundamental attributes compared to crops and the spatial and temporal dimensions of these attributes. A conceptual framework is also lacking for assessing and comparing the potential CSA synergies and tradeoffs that different livestock systems and interventions may generate. In this paper we aim to offer guidance on the operationalization of the CSA approach in the livestock sector. We draw on a literature review to explore the essential attributes of livestock systems in SSA as they relate to CSA objectives over different temporal and spatial scales. Based on this review, we propose a practical and flexible framework for assessing and comparing the synergies and tradeoffs that different livestock systems may generate among food security and climate change objectives over different spatial and temporal scales. The framework consists of four elements: CSA pillars, spatial-temporal scales, CSA objectives mapped to each spatial-temporal scale, and indicator guidance. Using farm survey data and national statistics, an illustrative application of the framework to two dairy farms in Rwanda is presented and discussed. The illustrative application demonstrates how the framework can be used to identify important, spatial-temporal CSA synergies and tradeoffs that otherwise may go unrecognized. Additional applications are needed to assess the utility, practicality, and potential of the framework to guide CSA operationalization in the livestock sector in SSA. Maximizing synergies and reducing tradeoffs among food security and climate change outcomes in the livestock sector is critical for a sustainable food future. With an emphasis on flexibility for tailoring to specific development contexts and compatibility with varying levels of data availability and methodological complexity, the framework is intended to support diverse stakeholders involved in policy and development seeking to identify those livestock systems that contribute most to food security and climate change objectives over time and space. [Display omitted] •Maximizing synergies among food security & climate change in the livestock sector is critical for a sustainable future.•However, the climate-smart agriculture (CSA) approach has not been fully operationalized in livestock sector development.•Spatial & temporal dimensions determine when, where, and for whom CSA synergies & tradeoffs in the livestock sector arise.•We propose a spatial-temporal framework to assess and compare the CSA synergies & tradeoffs of different livestock systems.•Applying the framework can help identify important CSA synergies & tradeoffs that otherwise may go unrecognized.